2021
DOI: 10.5194/cp-17-1989-2021
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and sustained environmental responses to global warming: the Paleocene–Eocene Thermal Maximum in the eastern North Sea

Abstract: Abstract. The Paleocene–Eocene Thermal Maximum (PETM; ∼ 55.9 Ma) was a period of rapid and sustained global warming associated with significant carbon emissions. It coincided with the North Atlantic opening and emplacement of the North Atlantic Igneous Province (NAIP), suggesting a possible causal relationship. Only a very limited number of PETM studies exist from the North Sea, despite its ideal position for tracking the impact of both changing climate and NAIP activity. Here we present sedimentological, mine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 152 publications
2
8
0
Order By: Relevance
“…A more local influence from bottom currents, such as reworking of the turbidite deposits (Faugères & Mulder, 2011; Rebesco et al., 2014) or of the hemipelagic suspension fall‐out appears more likely. The Early Palaeocene increasingly warmer and wetter climate (Stokke et al., 2021 and references within) is likely to have caused elevated weathering and runoff rates in the sediment source areas (e.g. Sømme et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A more local influence from bottom currents, such as reworking of the turbidite deposits (Faugères & Mulder, 2011; Rebesco et al., 2014) or of the hemipelagic suspension fall‐out appears more likely. The Early Palaeocene increasingly warmer and wetter climate (Stokke et al., 2021 and references within) is likely to have caused elevated weathering and runoff rates in the sediment source areas (e.g. Sømme et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The PETM was a complex event: in addition to global temperature increase (Dunkley Jones et al, 2013), some sea surface temperature and continental proxies hint to a transient warming prior to the CIE onset (Secord et al, 2010; Paleoceanography and Paleoclimatology 10.1029/2023PA004756 Sluijs et al, 2007), while marine environments display highly variable regional and local water column salinity and stratification (Sluijs & Brinkhuis, 2009). Areas proximal to the NAIP emplacement area, such as the North Sea, may have faced far more direct and local consequences to the tectonic uplift and sill intrusions, such as precursor cooling from volcanic SO 2 injections (Stokke et al, 2021), which are not observed in other distal locations globally. Alternatively, the tectonic uplift resulting from NAIP emplacement might have caused an episodic cooling event by modifying the positioning of the Northern Hemisphere jet stream (Vickers et al, 2024).…”
Section: Precursor Signals and An Naip Trigger For The Petmmentioning
confidence: 99%
“…Previous records of bottom water oxygen depletion in the North Sea region are not sufficiently resolved to identify whether basin restriction facilitated, or drove, the observed anoxia/euxinia around the PETM onset (e.g., Schoon et al., 2015; Stokke et al., 2021). The exact phasing between the emplacement of the NAIP, North Sea basin restriction, primary productivity and runoff changes and bottom water anoxia/euxinia has not yet been robustly determined, mainly due to the lack of high‐resolution records from high quality core material.…”
Section: Introductionmentioning
confidence: 99%
“…The short-lived PETM climate event lasting 100-200 kyr is known to have been associated with significant global warming (Sluijs et al, 2007), changes in the hydrological cycle and increasing sediment supply to North Atlantic basins (e.g., Dypvik et al, 2011;Kender et al, 2012;Pogge von Strandmann et al, 2021;Rush et al, 2021;Stokke et al, 2021;Jin et al, 2022).…”
Section: Stratigraphic Expression Of the Petm In The Froan Basinmentioning
confidence: 99%
“…Studies of the PETM suggest that this hypothermal event was associated with increased onshore weathering rates, higher seasonal variability in fluvial discharge and change in sediment delivery to shallow and deepwater basins (Pujalte et al, 2015;Carmichael et al, 2017;Rush et al, 2021;Jin et al, 2022), producing a stratigraphic response that can be distinguished from more long-term tectonic forcing (Samanta et al, 2016). Even though the PETM has been recognized several places in wells and outcrops in the North Atlantic (e.g., Beerling and Jolley, 1998;Dypvik et al, 2011;Harding et al, 2011;Kender et al, 2012;Eldrett et al, 2014;Stokke et al, 2021;Jolley et al, 2022), little is known about how the PETM influenced the dynamics of sedimentary systems in this region. However, recent studies from the North Sea suggest increased sediment supply and a change in depositional style during the event (Sømme et al, 2019;Vieira and Jolley, 2020;Jin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%